Evaluation of somatotype in artistic gymnastics competitors: a meta-analytical approach - Sterkowicz-Przybycien, K.; Gualdi-Russo, E. (The Journal of Sports Medicine and Physical Fitness, 2019)
INTRODUCTION: Studies on the anthropometric characteristics of athletes have a long history, but there are no published reviews on the somatotype of artistic gymnasts. Practitioners and professional coaches can gain guidance from improved understanding of the ideal body constitution and the impact of high-intensity training since preadolescence on body build. The present review is designed to provide this information. EVIDENCE ACQUISITION: Academic Search Complete, SPORTDiscus, Medline, Google Scholar, and ResearchGate were searched in January 2017. All studies on the body composition of male artistic gymnasts were included. We identified 19 studies assessing somatotype in male gymnasts. EVIDENCE SYNTHESIS: We found high heterogeneity of somatotype components between younger gymnasts (=18 years) and older gymnasts (>18 years) (1.6±0.3, 5.4±0.8, 3.0±0.6 vs. 1.8±0.4, 5.9±0.6, 2.2±0.4). Four different somatotypes resulted from the literature analysis, and ectomorphic mesomorph was the prevalent somatotype in both younger and older athletes. The main result showed a significant difference in ectomorphy (lower in older gymnasts than in younger gymnasts). CONCLUSIONS: Proper interpretation of the literature data may inform future research and enable professional coaches to longitudinally monitor gymnasts` somatotype components during growth and in talent identification. More research is needed to better understand the most suitable somatotype variations related to the different apparatuses used in artistic gymnastics.